Chemical characterizations of neurotransmission receptors of human and plant to unfold the evolutionary relationships among them. (June 2022) - Sengupta, Antara; Chakraborty, Subhadip; Pal Choudhury, Pabitra
Abstract: Vertebrates have very well defined nervous systems. A group of researchers hypothesize that plant also has an alternative sort of sensitive nervous system. They find a close relationship of the neurotransmission mechanism of animal with that of the plant and suspect a close relationship in amino acid transport mechanism among both the organisms. Although the protein structure is conserved more than molecular sequences, but the 3D structure of protein is largely influenced by the amino acid residues in the interior part of it. The constituents of a primary protein sequence have a variety of biochemical information which control the structure, function and stability of the protein. Hence, in this present study it is tried for characterization and comparison of neurotransmission receptors associated with human and plant to unfold the evolutionary relationships among them in bio-molecular level based on the chemical properties of the amino acids. The protein sequences of ionotropic glutamate receptor and GABA receptor of human (from vertebrate) and Arabidopsis thaliana (from plant) are considered as datasets. The 20 standard amino acids are classified into 8 chemical groups and are identified by specific numeric values. Alignment-based methods are used to identify the identical and similar amino acids among the aligned sequences.The common pattern finding procedure finds some conserved regions in the receptor protein sequences of both the species. The proximity between the protein sequences are calculated based on the distribution of each chemical group (in percentage) in them and phylogenetic trees are constructed to show the evolutionary relationships of neurotransmission receptors of both the species. The conventional multiple sequence alignment (MSA) method is also applied on the datasets and the results are compared. The analysis is further extended to structural level to understand the extent to which the animal and plant proteins are similar. Graphical Abstract: ga1 Highlights: ·The 20 standard amino acids are classified based on their 8 chemical properties. Chemical characterization of neurotransmission receptors of human and Arabidopsis thaliana are performed based on it. Conserved regions are identified in the primary protein sequences based on 8 chemical groups. ·Common patterns of various lengths are found in the receptor protein sequence of both the species. · Similarities among the neurotransmission receptors of both the species are calculated at sequence and structural level.